Acoustic Absorption Characteristics of Porous Asphalt Containing Coconut Shells - Norhafizah, Manap; Putra Jaya, Ramadhansyah; Muhammad Nazri, Borhan; Norhashidah, Manap; Juraidah, A. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In this study, coconut shells were used as aggregate replacement in porous asphalt to observe its effect on sound absorption through Impedance Tube test. For coconut shells aggregate porous asphalt to be used in realistic situations it is essential to ensure its mix integrity, resistance to oxidation and raveling as well as its durability; therefore, the Cantabro Test, Binder drain-down test and Theoretical Maximum Density were also conducted in this study. The result showed that porous asphalt containing coconut shells exhibited significance improvement of sound absorption. The sound absorption coefficient of porous asphalt incorporating 10%, 30% and 50% of coconut shells approximately at the peak of the curve which is at the frequency of 850hz are 0.93, 0.96 and 0.93 while for conventional porous asphalt is 0.89. This study also found that porous asphalt containing 10 - 50% of coconut shells contributed a significance improvement in sound absorption compare than conventional porous asphalt at the frequency of 200 – 1600 Hz. However, only porous asphalt containing 10% of coconut shells satisfied all the parameters tested similar to the conventional porous asphalt.